Disulfide bond-related gene signature development for bladder cancer prognosis prediction and immune microenvironment characterization - Hua Huang; Haiyan Shao; Yifan Wang; Lili Ge (Scientific Reports)
Abstract Bladder cancer is the fourth most common malignant tumor in men, with limited therapeutic biomarkers and heterogeneous responses to immunotherapy. Disulfide bond-driven cell death has emerged as a critical regulator of tumor progression and immune microenvironment remodeling. By integrating data from TCGA and GEO cohorts, we developed a Disulfide-Related Prognostic Signature (DRPS) using ten machine learning algorithms. Single-cell RNA sequencing (scRNA-seq) elucidated the cell subtype-specific expression patterns of disulfide bond regulatory genes, while immune microenvironment and drug sensitivity analyses validated its clinical translational potential. qRT-PCR experiments confirmed differential expression patterns of core genes in bladder cancer cell lines. The DRPS model, optimized by the StepCox[backward] algorithm, demonstrated robust prognostic accuracy across four validation cohorts (mean C-index = 0.658). High-risk patients exhibited an enhanced immunosuppressive microenvironment characterized by infiltrated activated cancer-associated fibroblasts, upregulated APC co-inhibition pathways, and elevated immune checkpoint expression. Notably, high DRPS scores were associated with primary resistance to immunotherapy but showed increased sensitivity to anti-tumor agents such as Elephantine and Leflunomide. This study establishes a novel DRPS that serves as a predictive indicator for bladder cancer prognosis and pan-cancer immunotherapy efficacy.